Analysis of the Microsurgery Match from 2014 to 2018 Reveals Increased Competition for Microsurgery Fellowship Positions - Cooper, Michael N.; Daneshgaran, Giulia; Yu, Roy; Chang, Jeff; Vartanian, Emma; Shamsunder, Meghana; Mehrara, Babak J.; Matros, Evan M.; Wong, Alex K. (Journal of Reconstructive Microsurgery, 2019)
Background There has been no peer-reviewed published data analyzing the microsurgery match since it was established. The aim of this study is to present and analyze match data to inform residents and programs regarding outcomes.Methods Anonymized data were requested from the San Francisco Match, which was plotted and analyzed utilizing Pearson's Chi-square, unpaired t-test, and one-way analysis of variance (ANOVA).Results Match data was obtained from the years 2014 to 2018. The match rate decreased from 84.6% in 2015 to 67.3% in 2018, mean = 73.7 (8.29%), and (p = 0.01735). The position fill rate fluctuated from 82.9% in 2014 to 90.0% in 2016, mean = 86.5 (3.0%). In 2014 and 2015, 66.7% of applicants matched their first or second choice compared to 48.0% in 2018, mean = 58.7 (8.3%), (p =.04785). Matched applicants ranked mean = 6.6 (1.4%) programs versus 3.4 (1.3) for unmatched, (p < 0.0001). Filled programs ranked a greater number of applicants per position, mean = 8.5 (1.8%), compared to partially filled, mean = 4.6 (2.6%), and unfilled mean = 3.6 (3.4%), programs (p = 0.0014). In 2015, 55.0% of programs matched their first or second choice compared to 30.4% of programs in 2018, mean = 43.0 (10.1%).Conclusion The application process for microsurgery has become more competitive. Matched applicants rank more programs than do unmatched. Fully filled programs rank more applicants per position than do unfilled or partially filled. Applicants and programs are increasingly less likely to match their top choices.
Keywords: microsurgery match; microsurgery fellowship; plastic surgery fellowship; San Fransisco match